2023
DOI: 10.15252/embr.202256233
|View full text |Cite
|
Sign up to set email alerts
|

DOT1L activity affects neural stem cell division mode and reduces differentiation and ASNS expression

Abstract: Cortical neurogenesis depends on the balance between self‐renewal and differentiation of apical progenitors (APs). Here, we study the epigenetic control of AP's division mode by focusing on the enzymatic activity of the histone methyltransferase DOT1L. Combining lineage tracing with single‐cell RNA sequencing of clonally related cells, we show at the cellular level that DOT1L inhibition increases neurogenesis driven by a shift of APs from asymmetric self‐renewing to symmetric neurogenic consumptive divisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…In the presence of limiting amounts of NPM1, H3K79me2 enrichment at the promoter of chromatin binding genes correlates with variable changes in their expression. Although we did not detect strong changes in the transcription of DOT1L target genes upon NPM1 KD, these subtle changes are expected in agreement with DOT1L being a modulator of transcription rather than a transcriptional activator [ 2 , 20 , 21 ]. Seemingly, H3K79me2 increased at the promoter of Ezh2 upon NPM1 KD (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In the presence of limiting amounts of NPM1, H3K79me2 enrichment at the promoter of chromatin binding genes correlates with variable changes in their expression. Although we did not detect strong changes in the transcription of DOT1L target genes upon NPM1 KD, these subtle changes are expected in agreement with DOT1L being a modulator of transcription rather than a transcriptional activator [ 2 , 20 , 21 ]. Seemingly, H3K79me2 increased at the promoter of Ezh2 upon NPM1 KD (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…One alternative scenario could be that upon NPM1 KD, DOT1L recruitment at peri-nucleolar heterochromatin affects chromatin accessibility, favoring binding of EZH2, and increasing H3K27me3 at DNA repeats, independent from a direct transcriptional control of Ezh2 . In this regard, we have previously demonstrated that in neural progenitor cells, DOT1L inactivation leads to reduced H3K27me3 levels at selected target genes, without impacting Ezh2 expression, but by altering PRC2 recruitment [ 2 ]. Alternatively, it is also possible that EZH1 replaces EZH2 functions and increases H3K27me3 at non canonical target genes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1D) has been shown to depend on the catalytic activity of Tet1 and Tet2 in ESCs (Mulholland et al, 2020), suggesting that TDG acts in concert with and downstream of 5mC oxidation at these genes. The down-regulation of Asns in the context of an inhibition of neural differentiation in TDG-null ECCs is reminiscent of the negative influence of low Asns levels on the differentiation of neural stem cells and the association of Asns mutations with a microcephaly phenotype in human (Ruzzo et al, 2013; Appiah et al, 2023). Collectively, these data suggest that, in a model recapitulating EpiSC differentiation into NMPs followed by a bifurcation towards neural or mesoderm fates, TDG favors the acquisition of a neural fate, possibly through the regulation of ATF4-dependent gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals the H3K79 methyltransferase DOTL1 mediates neurogenesis and neuronal energy metabolism. 66 , 67 DOT1L in C. elegans has been shown to regulate H3K9me2 in enhancer regions and regulate RNAi efficiency through suppression of heterochromatin, thus eliciting a global impact on gene expression. 56 , 57 Interestingly, in mammals, histone modification enzymes are also among the X chromosomal inactivation (XCI) escapee genes that are found to be expressed from the inactivated X chromosome.…”
Section: Discussionmentioning
confidence: 99%